Emotional Intelligence as a Factor of Successful Self-Realization in Students of Socionomic and Bionomic Professions - Obukhova, Y.V.; Borokhovski, E.F. (Psihologičeskaâ nauka i obrazovanie, 2021)
Self-realization is an important factor of successful social adaptation, especially in the early stages of a professional career in the dynamic conditions of the modern economy and society.The purpose of this study was to assess the general level of self-realization of students in socionomic and bionomic professions.It also performed comparative analysis (previously insufficiently represented in the empirical literature) of subjective perception of self-realization, depending on the length of professional training and the level of emotional intelligence.The subjects were students of the Southern Federal University, 109 representatives of socionomic and 75 of bionomic professions.The respondents completed a multidimensional self-realization questionnaire (S.I.Kudinov) and the test of emotional intelligence (EmIn, by D.V.Lucin).The study found significant differences between the representatives of the two professional types as in their subjective assessment of success of three types of self-realization, as in the direction and relative contribution to the subjective sense of self-realization of the two factors under consideration: duration of professional training and the level of emotional intelligence.Emotional intelligence was a significant predictor of all types of self-realization, compensating for the negative influence of duration of training in bionomic professions and enhancing its positive effect in socionomic professions.The authors emphasize the importance of developing and using specialized innovative programs for effective training of emotional intelligence as one of the key components in the work of practical psychologists with young people in the early stages of professional training and career. Представлены материалы исследования оценки общего уровня субъективного восприятия успешности трех видов самореализации молодых взрослых, специализирующихся в профессиях социономического и биономического типов, в зависимости от стажа обучения и выраженности эмоционального интеллекта. Авторы обращают внимание на то, что самореализации во всех сферах жизнедеятельности — важный фактор успешной социальной адаптации, в особенности на ранних этапах профессиональной карьеры в динамичных условиях современной экономики и общества в целом. Целью настоящего исследования была оценка общего уровня и сравнительный анализ (ранее недостаточно представленный в эмпирической литературе) субъективного восприятия успешности трех видов самореализации молодых взрослых, специализирующихся в профессиях социономического и биономического типов, в зависимости от стажа обучения и выраженности эмоционального интеллекта. Респонденты (109 представителей социономических и 75 — биономических профессий, студенты Южного федерального университета) заполнили многомерный опросник самореализации С.И. Кудинова и диагностическую методику эмоционального интеллекта ЭмИн Д.В.Люсина. Анализ полученных данных констатировал существенные различия между представителями двух профессиональных типов как в субъективной оценке ими уровня успешности личностной, социальной и профессиональной самореализации, так и в направленности и относительном вкладе факторов стажа обучения и выраженности эмоционального интеллекта в субъективное чувство самореализации. Эмоциональный интеллект был значимым предиктором всех видов самореализации, компенсируя негативное влияние фактора продолжительности обучения у представителей биономических профессий и усиливая его положительный эффект — у представителей социономических профессий. Авторами подчеркивается актуальность и важность разработки и применения специализированных инновационных программ эффективного тренинга эмоционального интеллекта в работе практических психологов с молодежью на ранних этапах обучения и профессиональной карьеры.